Performance of RT-PCR on Saliva Specimens Compared With Nasopharyngeal Swabs for the Detection of SARS-CoV-2 in Children: A Prospective Comparative Clinical Trial. Issue 8 (12th July 2021) - Fougère, Yves; Schwob, Jean Marc; Miauton, Alix; Hoegger, Francesca; Opota, Onya; Jaton, Katia; Brouillet, Rene; Greub, Gilbert; Genton, Blaise; Gehri, Mario; Taddeo, Ilaria; D'Acremont, Valérie; et al.
Abstract : Background: Saliva reverse transcriptase-Polymerase chain reaction (RT-PCR) is an attractive alternative for the detection of severe acute respiratory syndrome coronavirus 2 in adults with less known in children. Methods: Children with coronavirus disease 2019 symptoms were prospectively enrolled in a 1-month comparative clinical trial of saliva and nasopharyngeal (NP) RT-PCR. Detection rates and sensitivities of saliva and NP RT-PCR were compared as well as discordant NP and saliva RT-PCR findings including viral loads (VLs). Results: Of 405 patients enrolled, 397 patients had 2 tests performed. Mean age was 12.7 years (range, 1.2–17.9). Sensitivity of saliva was 85.2% (95% confidence interval: 78.2%–92.1%) when using NP as the standard; sensitivity of NP was 94.5% (89.8%–99.2%) when saliva was considered as the standard. For a NP RT-PCR VL threshold of ≥10 3 and ≥10 4 copies/mL, sensitivity of saliva increases to 88.7% and 95.2%, respectively. Sensitivity of saliva and NP swabs was, respectively, 89.5% and 95.3% in patient with symptoms less than 4 days ( P = 0.249) and 70.0% and 95.0% in those with symptoms ≥4–7 days ( P = 0.096). The 15 patients who had an isolated positive NP RT-PCR were younger ( P = 0.034), had lower NP VL (median 5.6 × 10 3 vs. 3.9 × 10 7, P < 0.001), and could not drool saliva at the end of the sampling ( P = 0.002). VLs were lower with saliva than with NP RT-PCR (median 8.7 cp/mL × 10 4 ; interquartile range 1.2 × 10 4 –5.2 × 10 5 ; vs. median 4.0 × 10 7 cp/mL; interquartile range, 8.6 × 10 5 –1 × 10 8 ; P < 0.001). Conclusions: While RT-PCR testing on saliva performed more poorly in younger children and likely after longer duration of symptoms, saliva remains an attractive alternative to NP swabs in children.